(untitled) (Conferencea, 2022)
The geographical position of the countries of Central Asia, which do not have maritime borders, is the main obstacle to maritime trade and access to major world markets. Moreover, geographical conditions within Central Asia itself, such as natural borders in the form of difficult mountain ranges, as well as political, cultural, historical contradictions in relations and weak institutions, create additional obstacles that turn into trade costs both between countries within the region and in trade with the outside world. Given these circumstances, the formation of an economic policy that will promote regional cooperation and trade seems to be a rather difficult task. However, the potential benefits of using internal trade routes and being close to huge markets such as the EU, China, Russia and India far outweigh the natural and institutional costs. On average, intra-regional trade in Central Asia accounts for less than five percent of total trade, and under existing trade models, the potential value of trade in it could be doubled (Lord, 2015). One of the main reasons for this geographically unbalanced foreign trade of the Central Asian states is the predominance of mineral resources. The export of raw materials, especially hydrocarbons, has helped the countries of Central Asia grow rapidly, overcome certain economic problems such as extreme poverty, and implement large infrastructure projects despite geographic, geopolitical and institutional shortcomings, and in some cases (Turkmenistan), in the absence of real market reforms (Batsaikhan and Dabrowski 2017).